Woody Woodpecker [videorecording (DVD)] - Lantz, Walter (Universal Pictures Home Entertainment, 2019)
Woody Woodpecker is back with his signature laugh, wacky antics and wisecracks in his first ever live-action/animated film. Woody must protect his forest home from Lance Walters, who starts building his dream mansion in the forest with his son, Tommy, and fiancě, Vanessa. To make matters worse, Woody must avoid the clutches of two grizzly poachers. With a series of crazy hijinks to sabotage their plans, Woody proves he will stop at nothing to defend his turf.